1991
DOI: 10.1111/j.1600-0714.1991.tb00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Gliadin antibodies identify gluten‐sensitive oral ulceration in the absence of villous atrophy

Abstract: This study demonstrates gluten-sensitive recurrent oral ulceration (ROU) in the absence of gastrointestinal abnormalities which is associated with a humoral response to wheat protein. Ten patients with severe ROU were investigated; all had normal small intestinal biopsies. Four patients had raised levels of antibodies to alpha gliadin, a wheat protein fraction; in three of these four, the ulceration remitted on treatment with a gluten-free diet (G.F.D.) and relapsed on gluten challenge. None of the remaining s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…(Table 3). Rose et al (24) and O'Farrelly et al (25) reported that it was unnecessary to perform jejunal biopsy in patients with RAS. In our study group, which included 82 patients, 3 (3.6%) were AGA IgG positive and 2 (2.4%) were AGA IgA positive, whereas in the control group that included the same number of patients, 1 (1.2%) was AGA IgG and AGA IgA positive.…”
Section: Discussionmentioning
confidence: 99%
“…(Table 3). Rose et al (24) and O'Farrelly et al (25) reported that it was unnecessary to perform jejunal biopsy in patients with RAS. In our study group, which included 82 patients, 3 (3.6%) were AGA IgG positive and 2 (2.4%) were AGA IgA positive, whereas in the control group that included the same number of patients, 1 (1.2%) was AGA IgG and AGA IgA positive.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of gluten-free diet (GFD) on remission of RAS is still uncertain, as dietary withdrawal of gluten occasionally results in significant benefit whereas some studies reported it ineffective [11,35,36]. Four patients accepted to start GFD, and all of them showed a significant improvement within 2–6 months after beginning of GFD.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient developed gastrointestinal abnormalities consistent with coeliac disease after clinical manifestations of sensitivity to gluten were confined to the oral cavity for a prolonged time. Our group's previous study of 10 patients with sensitivity to gluten and recurrent oral ulcers showed clinical and serological relapse after challenge with gluten, although there was no histological or symptomatic evidence of gastrointestinal disease 4. This patient also showed no abnormality in the three original biopsy specimens of small intestine taken when oral ulcers were present.…”
Section: Discussionmentioning
confidence: 58%